EPIDEMIOLOGICAL AND CLINICAL FEATURES OF BACTERIAL PURULENT MENINGITIS IN CHILDREN OF MOSCOW - L. N. Mazankova; G. D. Guseva; I. A. Soldatova (LLC "Diagnostics and Vaccines", 2018)
Data on etiology, epidemiology, clinical course and consequences of bacterial purulent meningitis in children of the city of Moscow are presented. The analysis of the dynamics of morbidity for the last 5 years is presented depending on etiology. In Moscow in recent years, there has been a change in serovars of meningococcus with an increase in W135, an increase in the proportion of pneumococcus and a decrease in the proportion of haemophilic type b. The modern aspects of the clinic, diagnosis, therapy and prevention of meningitis in children are considered.